2017
DOI: 10.4103/1793-5482.215783
|View full text |Cite
|
Sign up to set email alerts
|

Scrotal migration of tubing: An unusual complication after ventriculo-peritoneal shunt

Abstract: Scrotal migration of peritoneal end of ventriculo-peritoneal (VP) shunt into the patent processus vaginalis (PPV) is a rare complication. Its exact incidence is not mentioned in the literature till date. This may be because of the rarity of this complication, and also because all previous articles related to the complication were case reports. We, in our series, had an incidence of 0.9%. This prospective study has been conducted on 437 patients in the age group of 1 month–3 years who underwent VP shunt for hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The incidence of a hernia manifesting after shunt insertion has been reported to be 16.8 per cent, and predominantly involves the right side. 6 This is consistent with the general paediatric population in which 60 per cent of hernias also occur on the right due to the later 2 A persistent PV (PPV), along with its more vertically oriented canal during infancy, increases the risk of congenital hydrocele, with a peak incidence of 30 per cent during the first 2 months of life, then falling sharply to 10 per cent by the end of the first year. 11 The same anatomical factors might also predispose shunted infant patients to distal catheter herniation into the scrotal sac.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The incidence of a hernia manifesting after shunt insertion has been reported to be 16.8 per cent, and predominantly involves the right side. 6 This is consistent with the general paediatric population in which 60 per cent of hernias also occur on the right due to the later 2 A persistent PV (PPV), along with its more vertically oriented canal during infancy, increases the risk of congenital hydrocele, with a peak incidence of 30 per cent during the first 2 months of life, then falling sharply to 10 per cent by the end of the first year. 11 The same anatomical factors might also predispose shunted infant patients to distal catheter herniation into the scrotal sac.…”
Section: Discussionsupporting
confidence: 80%
“…It is well known that male paediatric patients with VP shunts have an increased risk of hernia and hydrocele when compared with normal children, but in the most extreme cases, shunt hardware can migrate into the scrotum. The incidence of a hernia manifesting after shunt insertion has been reported to be 16.8 per cent, and predominantly involves the right side . This is consistent with the general paediatric population in which 60 per cent of hernias also occur on the right due to the later descent of the right testis with subsequent delayed obliteration of the PV.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment can be conservative, based on respiratory rehabilitation, or surgical. There is not consensus as to which is the most appropriate [6,7].…”
Section: Journal Of Head Neck and Spine Surgery Discussionmentioning
confidence: 99%
“…16 Increased intraabdominal pressure stops the closing of processus vaginalis and later this helps in shunt herniation. 17 It is also reported that scrotal shunt migration has an association with the formation of hernias in children (right -60%, left -30%, bilateral -10%). 5 The residual peritoneal volume is linearly correlated with the body surface area at approximately 80 ml/m 2 .…”
Section: Disscusionmentioning
confidence: 95%